Case report: Immunoadsorption therapy for anti-caspr1 antibody-associated nodopathy - Liu, Lili; Chen, Juanjuan; Zhang, Yue; Wu, Jun; Hu, Jun; Lin, Zhijian (Frontiers in Immunology, 2022)
Background and objectives Several autoantibodies against proteins located at the node of Ranvier has been identified in patients with chronic inflammatory demyelinating polyneuropathy (CIDP) in the last few years. Then a new concept, autoimmune nodo-paranodopathies was proposed. Cases of Caspr1 autoantibodies are the most rare. Here we describe an anti-Caspr1 nodopathy patient, summarized his clinical, physiological and pathological features. Case presentation We present the case of a 56-year-old male patient with proprioceptive loss, ataxia, coarse tremor and distal limb weakness without any painess and cranial involvement. Electrophysiological studies showed prolonged distal motor latencies, conduction slowing and reduced amplitude distal compound muscle action potential (CMAP) amplitude. Antibodies against the nodes of Ranvier in serum samples revealed a positive finding for the anti-Caspr1 antibody (1:10).Myelinated fiber loss could be revealed in nerve biopsy. Longitudinal ultrathin sections of the nodal region was discovered in electron microscope, the paranodal/nodal architecture was destructed. It was lack of transverse bands and enlargement of the space between the axon and the paranodal loops was seen. The patient improved obviously after three times immunoadsorption(IA) therapy. Conclusion Anti-Caspr1 nodopathy patient may present atypical symptoms without any neuropathic pain and cranial palsy. The destruction of paranodal/nodal architecture could be observed in nerve biopsy, which may be caused by the lost of axoglial complex formed by NF155, CNTN1 and Caspr1. Antibodies detection is important for the diagnosis, while IA therapy could be regarded as an option for the patients allergic to rituximab (RTX).